TINJAUAN GEOPOLITIK SEJARAH INVASI RUSIA KE UKRAINA TAHUN 2022 - Diva Firyal Athaaya (2024)
This research will observe the Russo-Ukrainian War of 2022 through a historical geopolitics lens, how Russian state-actors and media influenced and shaped the invasion that happened in 2022. Russian state actors, especially Putin, are known to hold onto a certain historical sentiment unhealthily, consistently pushing out the agenda of Ukraine being a singular whole entity with Russia, spreading out propaganda and forcing the masses to believe in the same sentiment as Putin and the Russian government. In history, Russia and Ukraine shared almost the same history, being direct neighbours to one another geographically, and Ukraine being under the Russian authority since the Tsardom and Soviet Union for more than 300 years. Years of oppression for the Ukrainian people were forgotten by Putin and the Russian government, painting a narrative that Russia is Ukraine's saviour resulted in Russia finally displaying their imperialistic desires by invading Ukraine. Multiple narrative were thrown by the Russians to justify the act of invasion, such as the goal to "denazify" Ukraine and to protect ethnic Russians in the Donbas region in Ukraine.